A robust strategy for the synthesis of miktoarm star copolymers by combination of ROP and photoinitiated free radical polymerization. (December 2018) - Simal Aykac, F.; Aydogan, Cansu; Yagci, Yusuf
Graphical abstract: Highlights: Photoinduced Polymerization via Type II photoinitiators. Synthesis of Miktoarm Star Copolymers. Metal-free Conditions. Combination of Ring Opening Polymerization and Free Radical Polymerization Techniques. Abstract: A novel approach for the synthesis of miktoarm star copolymers by the combination of ring opening polymerization (ROP) and Type II photopolymerization is described. The method pertains to the use of a multifunctional initiator, bearing primary hydroxyl and tertiary amine functionalities, for the sequential or simultaneous polymerization of vinyl and lactone monomers under mild conditions. In the first step, phosphazene base (P2 -t- Bu) catalyzed ROP of ε-caprolactone is accomplished. Subsequently, thus obtained poly(ε-caprolactone) with amine end groups was used as co-initiator for the polymerization of methyl methacrylate by utilizing conventional Type II photoinitiators. The structures, molecular weight characteristics and thermal properties of the polymers are analyzed by NMR, gel permeation chromatography (GPC) and differential scanning calorimetry (DSC) measurements, respectively.